Improving Student Wellbeing: Evidence From a Mixed Effects Design and Comparison to Normative Data - Andrew Kemp (Teaching of Psychology, 2024)
Background: The wellbeing of university students is deteriorating, highlighting a critical role for institutions to better support student wellbeing. Objective: The goal of this work is to determine whether a final-year undergraduate wellbeing science module, inspired by recent theoretical developments, improved wellbeing during the COVID-19 pandemic. Method: Participants (N = 128) completed a brief online questionnaire including the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) across baseline and follow-up assessments. Analysis involved 2 group (intervention, control) x 2 time (baseline T1, follow-up T2) mixed-effects ANOVA and one-sample t-tests to compare the intervention group with population-based norms for adults aged 16 – 75+. Results: A significant interaction effect was observed, reflecting an increase in wellbeing in the intervention group in T2 relative to T1. Comparisons with published norms, further highlighted the beneficial impact of the module. Conclusion: Encouraging connection to self, others and nature has beneficial impacts on wellbeing, consistent with a modern science of wellbeing. Teaching Implications: Students learn the latest wellbeing theory, spanning the individual to the planet, and engage with opportunities to improve wellbeing, broadly defined. Teaching materials are made freely available for instructors wishing to develop a similar module or adapt materials for other purposes.